2012
DOI: 10.1371/journal.pone.0040567
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Radiosensitizing Effect of Cholesterol-Coupled Dbait Molecule in Rat Model of Glioblastoma

Abstract: BackgroundGlioma is the most aggressive tumor of the brain and the most efficient treatments are based on radiotherapy. However, tumors are often resistant to radiotherapy due to an enhanced DNA repair activity. Short and stabilized DNA molecules (Dbait) have recently been proposed as an efficient strategy to inhibit DNA repair in tumor.Methodology/Principal FindingsThe distribution of three formulations of Dbait, (i) Dbait alone, (ii) Dbait associated with polyethylenimine, and (iii) Dbait linked with cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
(55 reference statements)
0
20
0
1
Order By: Relevance
“…In addition, an important challenge on the horizon will be to identify better methods of limiting side-effects, and avoidance of over-treatment in patients with radiation-insensitive tumours. Appropriate patient selection is essential and novel strategies for identifying radio-sensitive tumours and directly targeting radioresistance mechanisms are currently the focus of investigation in a series of clinical and pre-clinical trials [65-67]. These strategies will help enhance the oncological benefit conferred by IORT in more precisely stratified patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an important challenge on the horizon will be to identify better methods of limiting side-effects, and avoidance of over-treatment in patients with radiation-insensitive tumours. Appropriate patient selection is essential and novel strategies for identifying radio-sensitive tumours and directly targeting radioresistance mechanisms are currently the focus of investigation in a series of clinical and pre-clinical trials [65-67]. These strategies will help enhance the oncological benefit conferred by IORT in more precisely stratified patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…15 Briefly, 5 mL of tumor cell suspension in serum-free alpha-minimum essential medium were inoculated under anesthesia: 5% isoflurane for induction and 2.5% for maintenance in air. Bupivacaine (8 mg/kg; Centravet) was subcutaneously injected before incision to prevent postoperative pain.…”
Section: Animal Modelmentioning
confidence: 99%
“…We previously showed Dbait to be effective in combination with radiotherapy on several radio-resistant tumors, both in vitro and in vivo (8,(11)(12)(13). Furthermore, studies on an intestinal tumor rodent model revealed that oral administration of Dbait, in association with the chemotherapy agents 5-fluorouracil and camptothecin leads to increased chemosensitization of intestinal tumors and to a low systemic exposure (14).…”
Section: Introductionmentioning
confidence: 99%